The Effect of Lidocaine Tetracaine Peel-off on Laser-Assisted Hair Removal Side Effects - Ali Asilian (مجله دانشکده پزشکی اصفهان, 2011)
• Background: Lidocaine7%-Tetracaine 7% is one of the materials recently offered for performing laser-assisted hair removal. The aim of this study was to compare the effects of this material with placebo on side effects of laser-assisted hair removal. • Methods: This clinical trial was carried out on 110 women referred to Isfahan Spadana laser clinic for laser-assisted hair removal. Lidocaine7%-Tetracaine7% was applied on one-half of the face, whereas placebo was applied on the other side to create local anesthesia and after 30 minutes the place was cleaned and was investigated for complications (edema, erythema, and pallor); then laser therapy was begin. In the end of the therapy, the patient’s pain was estimated based on VAS (Visual Analog Scale). The data was analyzed using SPSS software by chi square and paired t tests. • Finding: The mean age of patients was 27.74 ± 10.8 years. Average level of anesthesia 30 minutes after using Lidocaine7%-Tetracaine7% and placebo based on VAS were respectively 3.6 ± 1.4 and 8.4 ± 1.5 (P = 0.001). In other words, patients have felt less pain by using Lidocaine7%-Tetracaine7%. Frequency of complications in patients was not significantly different between two groups. • Conclusion: Considering the better effect of Lidocaine7%-Tetracaine7% compared to placebo and its minimal side effects, we can use it before perform laser-assisted hair removal.